The Collected Poems of Barbara Guest - Guest, Barbara (Book collections on Project MUSE., 2008)
"One of the most notable members of the New York School - and its best-known woman - Barbara Guest began writing poetry in the 1950s in company that included John Ashbery, Kenneth Koch, Frank O'Hara, and Tames Schuyler. And from the beginning, her practice placed her at the vanguard of American writing. Guest's poetry, saturated in the visual arts, extended the formal experiments of modernism, and played the abstract qualities of language against its sensuousness and materiality. Now, for the first time, all of her published poems have been brought together in one volume, offering readers and scholars unprecedented access to Guest's remarkable visionary work. The Collected Poems moves from her early New York School years through her more abstract later work, including some final poems never before published. Switching effortlessly from the real to the dreamlike, the observed to the imagined, this is poetry both gentle and piercing - seemingly simple, but truly and beautifully dislocating."--Jacket.